A high performance micro-pressure sensor based on a double-ended quartz tuning fork and silicon diaphragm in atmospheric packaging. (30th April 2015) - Cheng, Rongjun; Li, Cun; Zhao, Yulong; Li, Bo; Tian, Bian
Abstract: A resonant micro-pressure sensor based on a double-ended quartz tuning fork (DEQTF) and bossed silicon diaphragm in atmospheric packaging is presented. To achieve vacuum-free packaging with a high quality factor, the DEQTF is designed to resonate in an anti-phase vibration mode in a plane that is under the effect of slide-film damping. The feasibility is demonstrated by theoretical analysis and a finite element simulation. The dimensions of the DEQTF and diaphragm are optimized in accordance with the principles of improving sensitivity and minimizing energy dissipation. The sensor chip is fabricated using quartz and silicon micromachining technologies, and simply packaged in a stainless steel shell with standard atmosphere. The experimental setup is established for the calibration, where an additional sensor prototype without a pressure port is introduced as a frequency reference. By detecting the frequency difference of the tested sensor and reference sensor, the influences of environmental factors such as temperature and shocks on measuring accuracy are eliminated effectively. Under the action of a self-excitation circuit, static performance is obtained. The sensitivity of the sensor is 299 kHz kPa −1 in the operating range of 0–10 kPa at room temperature. Testing results shows a nonlinearity of 0.0278%FS, a hysteresis of 0.0207%FS and a repeatability of 0.0375%FS. The results indicate that the proposed sensor has favorable features, which provides a cost-effective and high-performance approach for low pressure measurement.